Percutaneous aspiration embolectomy is beneficial for pulmonary thromboembolism in adult patients with Fontan circulation. Issue 2 (August 2022) - Kodama, Hiroyuki; Shiina, Yumi; Kijima, Yasufumi; Nishihata, Yosuke; Niwa, Koichiro
Abstract: In patients with acute pulmonary thromboembolism (PTE), increased pulmonary vascular resistance (PVR) due to thrombus sometimes causes hemodynamic instability, requiring reperfusion therapy with drugs, surgery, or catheterization. In particular, patients with Fontan circulation, which is strongly affected by PVR, are prone to hemodynamic instability. Moreover, these patients sometimes have bleeding complications such as hemoptysis and intrathoracic adhesions, following multiple prior thoracotomies, making it difficult to choose pharmacotherapy. Percutaneous aspiration embolectomy (PAE) is a useful treatment option because it minimizes bleeding complications, is less invasive, and more rapid than surgery, and is easy to perform. Herein, we report two cases of Fontan patients having PTE treated with PAE. In Case 1, a 21-year-old man with a history of a Fontan procedure suddenly developed acute PTE, for which anticoagulants were administered immediately. However, his condition was refractory to treatment and he underwent PAE on the third day of illness. In Case 2, a 28-year-old woman with a history of Fontan procedure who had been on anticoagulants, developed acute PTE on the ninth postpartum day, and underwent PAE on the day of onset. In both cases, the respiratory condition improved, and re-treatment for PTE was not required. Learning objective: Fontan patients with acute pulmonary thromboembolism often require reperfusion therapy because they can easily become hemodynamically unstable due to increased pulmonary vascular resistance. For them, who often have adhesions following multiple prior thoracotomies and bleeding complications, percutaneous aspiration embolectomy may be effective as it has minimal bleeding risk and is minimally invasive, rapid, and straightforward.